Molecular Mechanisms of Bartonella and Mammalian Erythrocyte Interactions: A Review - Deng, Hongkuan; Pang, Qiuxiang; Zhao, Bosheng; Vayssier-Taussat, Muriel (Frontiers in Cellular and Infection Microbiology, 2018)
Bartonellosis is caused by Bartonella species that are distributed worldwide with animal and public health impact varying according to Bartonella and host species, immunological characteristics, infection phase and geographical region. Bartonella is widely distributed in ruminants, cats, dogs, rodents and other mammals including humans. At least 13 species or subspecies of Bartonella are zoonotic and each species appears to be highly adapted to a limited number of reservoir animals in which it is often asymptomatic. Bartonella infection may lead to a variety of clinical manifestations such as cat scratch disease, endocarditis, bacillary angiomatosis and bacillary peliosis in humans. As described in the B.tribocorum-rat model, when Bartonella was seeded into the blood stream, they could escape immunity, adhered to and invaded mature erythrocytes within 2 days. Once inside, they replicated and persisted in the infected erythrocytes for several weeks. This review summarizes our current understanding of how Bartonella prevent phagocytosis and complement activation, what pathogenesis factors are involved in erythrocyte adhesion and invasion, and how Bartonella could replicate and persist in mammalian erythrocytes. Current advances in research will help us to decipher molecular mechanisms of interactions between Bartonella and mammalian erythrocytes and may help in the development of biological strategies for the prevention and control of bartonellosis.